Comparative Analysis of Basic Movement Skills and BMI of Elementary School Students in Lower Grade Elementary School in Full Day and Regular Schools - Arya Dicka Nugraha; Helmy Firmansyah; Agus Gumilar (Universitas Negeri Semarang, 2026)
Differences in students daily physical activity patterns also contribute to variations in their fundamental movement skills. This study aims to analyze the comparison of basic movement skills and Body Mass Index (BMI) of low-grade elementary school students in schools with full day systems and regular schools. The research method used is quantitative and comparative with an ex post facto approach. The research sample amounted to 96 elementary school students in Cibeunying Kaler District, consisting of 48 regular school students and 48 full-day school students, with a simple random sampling technique. The research instrument used basic motion skill tests which included locomotor, non-locomotor, and manipulative movements, as well as BMI measurements based on WHO standards. Data analysis was carried out descriptively and inferentially using parametric statistical tests. The results of the study showed that the basic movement skills of regular school students were higher than that of full-day school students. In addition, full-day school students have a higher percentage of obesity BMI than regular school students. These findings suggest that differences in learning systems have the potential to affect physical activity, basic movement skills, and students' BMI conditions. The conclusion is that differences in the education system and BMI categories are associated with variations in students’ fundamental movement skills, where regular school students and those with normal BMI tend to demonstrate better performance.